PENGARUH PENGKONDISIAN AVERSI TERHADAP KECANDUAN BERMAIN GADGET PADA SISWA SMA MUHAMMADIYAH 1 PEKANBARU - Sartita T, Nova; Saam, Zulfaan; Umari, Tri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is motivated by the phenomenon of addiction to play gadget among students. This study aims to 1. To determine the level of addiction to play gadgets in high school students before given conditioning aversi. 2. To know the level of addiction to play gadgets on high school students after being given aversi conditioning. 3. To know the difference in the level of addiction to play gadgets on the students before and after given the conditioning aversi. 4. To know the effect of aversion conditioning on addiction to play gadgets in high school students. The subjects of this study were students of class X of SMA Muhammadiyah 1 with certain criteria that is as many as 23 people. The instrument of this research is questionnaire that is processed based on addiction aspect of playing gadget that is as much as 25 item statement. The results showed that the calculation coefficient of determinant obtained r2 = 0.3922 = 0.15 which means there is 15% contribution of group guidance service by using aversi conditioning technique to addicted to play gadget at student class X SMA Muhammadiyah 1 Pekanbaru while 85% more influenced by other factors. Based on the results of this study can be concluded that 1. Level of addiction to play gadgets on high school students before being given treatment mostly included in the high category. 2. Level of addiction to play gadgets on high school students after being given treatment mostly included in the low category. 3. There is a difference between the level of addiction to play gadgets on the students before the treatment is mostly in the high and medium category but after being given treatment, the level of addiction to play the student gadget mostly in the low category.4. The influence of group counseling services using aversion conditioning techniques on addiction to playing gadgets in high school students is low. Key Word : Conditioning Aversi, Gadget Play Addiction